PARENTS’ PERCEPTIONS OF ONLINE LEARNING METHODS: A QUANTITATIVE STUDY - Jhoanita NF; Siti Khadijah (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2022)
Online learning may alienate some students as they may be not familiar with it or face some problems such as students’ lack of concentration during online learning, poor internet services, the lack of suitable gadgets to access online learning. Parents, as ones who are responsible for the learning process of their children during online learning may be burdened with online learning approach. Therefore, it seems important to analyze the parents’ perceptions toward online learning to understand their concerns on the efficacy of online learning process. The present study uses a quantitative approach by distributing a set of questionnaires to 90 parents from a private school in Cirebon, Indonesia. The results of present study show that parents have relatively positive perceptions toward online learning. It can be said that online learning may have some merits toward students’ learning progress.